MEDICAL AND STATISTICAL CHARACTERISTICS OF BREAST CANCER IN ST. PETERSBURG FEMALE RESIDENTS - N. S. Romanenkov; V. V. Hizha; K. N. Movchan; U. M. Morozov; R. M. Gedgafov; A. S. Slobodkina (Исследования и практика в медицине, 2019)
Purpose. To analyze the main medical and statistical parameters, allowing to evaluate the results of breast cancer treatment. Patients and methods. Data on 4689 breast cancer (BC) patients were analyzed retrospectively. Inclusion criteria were: female, residence in St. Petersburg, diagnosis of BC established in 2011, 2012. The study also includes information on the options of BC surgical treatment, one-year mortality in breast cancer patients and index of the contingent accumulation in St. Petersburg in 2011–2017. For statistical data processing Statistica 12.0 for Windows, Population Cancer Register and MedInfo-4 were used. The differences in the groups of studies were considered statistically significant at p < 0.05.Results. The prevalence of breast cancer among women in St. Petersburg varies from 532.6 per 100 000 population in 2011 to 545.00/0000 in 2012. In 2011 the incidence of BC in women in St. Petersburg was 46.210/0000 (standard deviation 1.05) and in 2012 – 49.50/0000 (standard deviation 1.05). The mean age of breast cancer patients is 64 years (standard deviation 12.25). Localization of a tumor in one of the glands was found in 4617 (98.5%) clinical observations. In 2,846 (60.7%) cases, the tumor sizes varied from 2 to 5 cm. Signs of infiltrative ductal carcinoma were histologically verified in 3689 (80%) cases. The proportion of single-stage breast reconstruction after mastectomy in the overall structure of surgeries in breast cancer patients increased in 2011–2017 more than 6.5 times. The 5-year survival rate in study groups was 64.4% and 63.3%. Conclusions The main statistical parameters of medical care (MC) analysis in breast cancer patients in St. Petersburg in 2011–2017 allow to state generally positive trends in the anticancer fight organization. The increase of the breast cancer incidence rates is partly due to the improved quality of examination and treatment of patients through the creation in the city of a system of high-tech MC, as well as to the particularly wary of doctors in detecting breast tumors.